2000
DOI: 10.1103/physrevb.62.14049
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of quasicrystalline surfaces: Effects of surface preparation and bulk structure

Abstract: We elucidate the nature of the surface electronic properties of quasicrystalline Al-Pd-Mn. We do this by using photoelectron and Auger electron spectroscopies, and by making a variety of comparisons-across types of bulk samples, and across methods of surface preparation. The main conclusions are these: (i) The narrow Mn 2p 3/2 core-level line observed in the icosahedral phase is a fingerprint of a suppression in the density of states (a pseudogap) at the Fermi level and is not unique to the quasicrystalline ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 48 publications
5
32
0
Order By: Relevance
“…For i-Al-Pd-Mn, the Al 2p BE turns out to be 73.1 eV, which is in good agreement with the literature. 33 The bulk ͑arrow͒ and surface ͑tick͒ plasmon related features are observed at 16 and 10.4 eV loss energies, respectively. The plasmon energies are in agreement with the electron energy loss spectroscopy data.…”
Section: Resultsmentioning
confidence: 99%
“…For i-Al-Pd-Mn, the Al 2p BE turns out to be 73.1 eV, which is in good agreement with the literature. 33 The bulk ͑arrow͒ and surface ͑tick͒ plasmon related features are observed at 16 and 10.4 eV loss energies, respectively. The plasmon energies are in agreement with the electron energy loss spectroscopy data.…”
Section: Resultsmentioning
confidence: 99%
“…In any case, the existence of a deep pseudogap is an indication of a considerable degree of covalency in the interaction between the Al and the transition-metal atoms. 33 Previous investigations ͑both theoretical 30 and experimental 34 ͒ of the surface electronic structure of i-Al-Pd-Mn have demonstrated that the metallic character of the bonding is enhanced at the surface and that the pseudogap is partially leveled out as a consequence of a strong relaxation of the near-surface Al atoms. The present work extends these studies to the electronic structure of a well-ordered quasiperiodic adlayer and we find that the pseudogap has disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the sp states are strongly hybridized with the transition metal d states, leading to the formation of a strong suppression of the sp density of states at the Fermi level. Several experiments have shown that the pseudogap is maintained up to the first layers of the sputter-annealed surface [23]. The pseudogap in the partial sp DOS could thus be the origin of the electronic confinement within the metal thin films.…”
mentioning
confidence: 99%